Peter Seebergs immoralisme: Arkivets utrykte manuskripter fra perioden 1942-43 - Juhl Rasmussen, Anders (Danske Studier, 2016)
The article examines Seeberg’s earliest reading of Friedrich Nietzsche’s Thus Spoke Zarathustra, the lyrical poetry of Friedrich Hölderlin, and Oswald Spengler’s philosophy of history in The Decline of the West. It opens with a discussion of Seeberg’s high school essay on Adolf Hitler, taking stock of Marianne Juhl’s selective presentation of that essay in her monograph on Seeberg (1999). Seeberg’s idealization of Hitler was by no means an isolated event. In the period 1942-43, i.e., contemporaneous with his Hitler essay, Seeberg produced juvenilia consisting of eight plays, three novels, and a philosophical essay, registered (erroneously) as »12 plays« in his archive. This previously unknown archival material offers a new basis for understanding Seeberg’s decision in June 1943, at the age of 18, to travel to Berlin’s UFA studios.